About a challenging mediastinal tumor. (November 2015) - Mlika, Mona; Braham, Emna; Hamrouni, Rim; Zribi, Hazem; El Mezni, Faouzi
Mediastinal hemangiomas are rare, accounting for 0.5% of all mediastinal tumors. These tumors are challenging because of the lack of specific clinical and radiologic signs. We report a 10-year experience of 5 mediastinal hemangiomas in a single institution, with neurologic signs related to neuroforaminal extension in 2 cases. Surgical treatment was performed in all 5 patients, without complications after a follow-up period varying from 9 months to 2 years.